Large field-of-view movement-compensated intrinsic optical signal imaging for the characterization of the haemodynamic response to spreading depolarizations in large gyrencephalic brains - Schöll, Michael; Santos, Edgar; Sánchez-Porras, Renán; Kentar, Modar; Silos, Humberto; Zheng, Zelong; Gang, Yuan; Unterberg, Andreas; Sakowitz, Oliver; Dickhaus, Hartmut (Journal of cerebral blood flow & metabolism, 2017)
Haemodynamic responses to spreading depolarizations (SDs) have an important role during the development of secondary brain damage. Characterization of the haemodynamic responses in larger brains, however, is difficult due to movement artefacts. Intrinsic optical signal (IOS) imaging, laser speckle flowmetry (LSF) and electrocorticography were performed in different configurations in three groups of in total 18 swine. SDs were elicited by topical application of KCl or occurred spontaneously after middle cerebral artery occlusion. Movement artefacts in IOS were compensated by an elastic registration algorithm during post-processing. Using movement-compensated IOS, we were able to differentiate between four components of optical changes, corresponding closely with haemodynamic variations measured by LSF. Compared with ECoG and LSF, our setup provides higher spatial and temporal resolution, as well as a better signal-to-noise ratio. Using IOS alone, we could identify the different zones of infarction in a large gyrencephalic middle cerebral artery occlusion pig model. We strongly suggest movement-compensated IOS for the investigation of the role of haemodynamic responses to SDs during the development of secondary brain damage and in particular to examine the effect of potential therapeutic interventions in gyrencephalic brains.